Impact of Antidepressant Therapy on Cognitive Aspects of Work, Condom Use, and Psychosocial Well-Being among HIV Clients in Uganda. (October 2014) - Wagner, Glenn J.; Ngo, Victoria K.; Nakasujja, Noeline; Akena, Dickens; Aunon, Frances; Musisi, Seggane
Objective: Depression has been found to impede several health outcomes among people living with HIV, but little research has examined whether depression treatment mitigates this influence. We assessed the impact of antidepressant therapy on measures of work, condom use, and psychosocial well-being among depressed HIV clients in Uganda. Methods: Paired t -tests and McNemar tests were used to assess change in survey data collected from participants at initiation of antidepressant therapy (baseline) and 6 months later. Results: Ninety-five participants completed the 6-month assessment, of whom 82 (86%) responded to treatment (defined as Patient Health Questionnaire-9 score < 5). Among study completers, work functioning improved significantly, as did measures of self-efficacy related to condom use and work (as well as general self-efficacy), and internalized HIV stigma declined; however, actual engagement in work activity and consistent condom use did not show significant change. Similar findings were observed among treatment responders. Conclusions: Antidepressant treatment benefits functional capacity, psychological well-being, and cognitive intermediary factors that may be essential for behavioral change related to work and condom use, but supplementary therapeutic strategies may be needed to impact more direct behavioral change.